A decision-making method to choose optimal systems considering financial and environmental aspects: Application in hybrid CCHP systems. (1st July 2022) - Melo, F.M.; Magnani, F.S.; Carvalho, M.
Abstract: This work presents a decision-making method based on a multiobjective optimization model that integrates renewable and nonrenewable energy equipment and considers environmental and financial combined gains. Parametric studies optimize the system for other energy tariffs, and an investment risk analysis provides additional information about the systems identified by the decision-making method and in the parametric studies. The energy system is located in northeastern Brazil. The bicriteria optimal solution comprises a gas boiler, solar collector, photovoltaic panels, wind turbines, and absorption and compression chillers. This optimal solution had a reasonable commitment to financial and environmental present values. Another energy system was identified in the parametric study, where an engine-generator set and a recovery boiler were included. Both systems presented a significant gain in environmental present value versus a slight decrease in financial present value. In the risk analysis, these systems demonstrated high adaptability, mainly due to the integration of the absorption chiller and engine-generator set and cascading use of energy. This high adaptability led to low investment risks. Graphical abstract: Image 1 Highlights: The more complex the system, the lower the investment risk. Optimization focused on highest environmental and financial percentage gains. Bicriteria optimal has -73% emissions compared to purely financial solution. Bicriteria optimal has + 9% cost compared to purely environmental solution. Parametric study established two highly adaptable system configurations.